PERENCANAAN ARTIFICIAL REEF SEBAGAI RESTORASI TERUMBU KARANG DAN PENGAMAN PANTAIDI PULAU LEMUKUTAN KABUPATEN BENGKAYANG - Dhiecho Mahar Dhiecha (Universitas Tanjungpura, 2015)
ABSTRACT Damage that occurs around the area Lemukutan Island caused the use of chemicals or cyanide to catch fish and coral reefs by local people, but it is also often made use of bombs surrounding communities to take beautiful corals that will be sold to destroy coral reef ecosystems in the waters .Artificial reef planning methods (Artificial reef ) as the restoration of coral reefs and coastal protection is to conduct a field survey using a measuring instrument GPS topographic, marine water quality data and using secondary data, statistical data, tidal, wave height, bathymetry map, direction of flow and wind direction. Water quality analysis carried out in-situ, parameter test in the brightness of the water, currents, salinity, temperature, pH. Analysis of the function of Artificial reefs for reef restoration and as coastal protection is to use a hollow dome type or reef balls. Appropriate placement location and located at coordinates N 00 45 '33.8